Accelerated Life Testing and Its Application in the Field of Warranty Policy under Type-I Censoring Scheme - Alam, Intekhab; Uddin, Azhar; Ahmed, Aquil (Thailand Statistician, 2023)
In this paper, we describe how to propose and analyze the accelerated life testing plans to develop the excellence and reliability of the item for consumption. We also focus on finding the expected cost rate and the expected total cost for age replacement under pro rate rebate warranty policy. The problem is studied using constant stress, under the assumption that the lifetimes of the units follow the Fréchet failure model for predicting the cost of age replacement under the warranty policy. Asymptotic variance and covariance matrix of the estimators are obtained by using the Fisher information matrix. Confidence intervals for parameters and respective errors are also obtained. A simulation study is performed to illustrate the statistical properties.